Depression, anxiety and stress among patients with inflammatory bowel disease during the COVID-19 pandemic: Australian national survey. Issue 1 (12th February 2021) - Cheema, Madiha; Mitrev, Nikola; Hall, Leanne; Tiongson, Maria; Ahlenstiel, Golo; Kariyawasam, Viraj
Abstract : Background: The global COVID-19 pandemic has impacted on the mental health of individuals, particularly those with chronic illnesses. We aimed to quantify stress, anxiety and depression among individuals with Inflammatory bowel disease (IBD) in Australia during the pandemic. Methods: An electronic survey was made available to IBD patients Australia-wide from 17 June to 12 July 2020. Respondents with an underlying diagnosis of IBD and over 18 years of age were included. A validated questionnaire (Depression, Anxiety, Stress Score-21, DASS21) was used to assess depression, anxiety and stress. Data on potential predictors of depression, anxiety and stress were collected. Results: 352 participated in the survey across Australia. 60.5% of respondents fulfilled DASS criteria for at least moderate depression, anxiety or stress. 45% reported a pre-existing diagnosis of depression and/or anxiety. Over 2/3 of these respondents reported worsening of their pre-existing depression/anxiety due to the current pandemic. Of those without a pre-existing diagnosis of anxiety or depression, high rates of at least moderate to severe depression (34.9%), anxiety (32.0%) and stress (29.7%) were noted. Younger age (OR 0.96, 95% CI 0.94 to 0.98, p<0.001), lack of access to an IBD nurse (OR 1.81, 95% CI 1.03 to 3.19, p=0.04) and lack of education on reducing infection risk (OR 1.99, 95% CI 1.13 to 3.50, p=0.017) were associated with significant stress, anxiety and/or depression. Conclusion: High prevalence of undiagnosed depression, anxiety and stress was identified among respondents. Improved access to IBD nurse support and greater attention to education are modifiable factors that may reduce depression, anxiety and/or stress among patients with IBD during the pandemic.